Measurements of ash emissions from a plant for burning of radioactively contaminated wood - Ivasenko, Vitaliy; Shvayko, Volodymyr; Kulik, Nadiya; Havryliuk, Vladyslav (Technology audit and production reserves, 2017)
The object of research is the efficiency of dust and gas treatment equipment for the removal of contaminated combustion products from the flue gases of the incinerator plant. One of the most problematic areas of the research facility is that when removing contaminated combustion products (ash) from flue gases, the efficiency of the dust and gas treatment equipment should ensure ash concentrations of up to 4 mg/m3 in the incinerator plant emissions. Investigations were conducted in Chornobyl, Ukraine on an incinerator plant equipped with a gas stream cleaning system, and includes coarse and fine cleaning. Application of two-stage cleaning allows to increase the efficiency of dust and gas cleaning equipment and to reduce emissions of radiation ash. In order to confirm the design requirement for gas cleaning equipment, in which flue gas filtration should provide ash emissions to 4 mg/m3, experimental measurements are made during the operation of the incinerator plant. Based on the results of measurements of dust and gas cleaning equipment, the maximum ash concentration is 3.76 mg/nm3, which meets the requirements. This plant plays an important role in reducing emissions and reducing the ecological load of the region and improving the environmental safety of Ukraine.